Online dynamic cardiac imaging based on the elastic-net model. Issue 2 (1st February 2017) - Hong, Mingjian; Zhang, Haibiao; Lin, Mengran; Liu, Feng; Ge, Yongxin
Abstract: Purpose : The purpose of this work was to develop an online dynamic cardiac MRI model to reconstruct image frames from partial acquisition of the Cartesian k -space data, which utilizes structural knowledge of consecutive image frames. Materials and methods : Using an elastic-net model, the proposed algorithm reconstructs dynamic images using both L1 and L2 norm operations. The L1 norm enforces the sparsity of the frame difference, while the L2 norm with motion-adaptive weights catches the internal structure of frame differences. Unlike other online methods such as the Kalman filter (KF) technique, the new model requires no assumption of Gaussian noise, and can faithfully reconstruct the dynamic images within a compressive sensing framework. Results : The proposed method was evaluated using simulated dynamic phantoms with 40 frames of images (128 × 128) and a cardiac MRI cine of 25 frames (256 × 256). Both results showed that the new model offered a better performance than the online KF method in depicting simulated phantom and cardiac dynamics. Conclusion : It is concluded that the proposed imaging model can be used to capture a large variety of objects in motion from highly under-sampled k -space data, and being particularly useful for improving temporal resolution of cardiac MRI.